2015
DOI: 10.1111/nep.12533
|View full text |Cite
|
Sign up to set email alerts
|

Expressions of mRNA for innate immunity‐associated functional molecules in urinary sediment in immunoglobulin A nephropathy

Abstract: Aim It has been reported that the innate immune system plays a pivotal role in the pathogenesis of immunoglobulin A nephropathy (IgAN). To explore non‐invasive monitoring of disease activity in children with IgAN, we examined whether expressions of mRNA for innate immunity‐associated functional molecules: CC ligand chemokine 5 (CCL5), fractalkine/CX3CL1, interferon‐γ‐induced protein 10 (IP‐10), monocyte chemoattractant protein 1 (MCP‐1), retinoic acid‐inducible gene‐I (RIG‐I), and toll‐like receptor 3 (TLR3) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The broad functions of type I IFNs involve the expression of hundreds of IFN-stimulated genes (ISGs). Activation of TLR3/type I IFNs/ISGs axis by viral dsRNA may be important in antiviral host defense and in the onset or worsening of glomerular diseases such as lupus nephritis [6] and IgA nephropathy [7]. In addition, pseudoviral immune responses induced by self-damage-associated molecular patterns may also activate TLR3/ type I IFNs/ISGs axis in glomerulonephritis even in the absence of obvious viral infection [8].…”
Section: Introductionmentioning
confidence: 99%
“…The broad functions of type I IFNs involve the expression of hundreds of IFN-stimulated genes (ISGs). Activation of TLR3/type I IFNs/ISGs axis by viral dsRNA may be important in antiviral host defense and in the onset or worsening of glomerular diseases such as lupus nephritis [6] and IgA nephropathy [7]. In addition, pseudoviral immune responses induced by self-damage-associated molecular patterns may also activate TLR3/ type I IFNs/ISGs axis in glomerulonephritis even in the absence of obvious viral infection [8].…”
Section: Introductionmentioning
confidence: 99%
“…Nineteen ARMS subjects and 21 age‐ and sex‐matched healthy controls (HC) were enrolled in the study (Table 1). Because the molecular concentrations in urine greatly depend on kidney function, we measured urinary creatinine/albumin rates as renal function markers and nephritis markers (CX3CL1/fractalkine; Aizawa et al, 2013; Tsuruga et al, 2015). After confirming normality by F test, Student's t ‐test was used to analyse the results of measurement by Welch t ‐test in the ARMS and HC groups.…”
Section: Methodsmentioning
confidence: 99%
“…However, many new insights into the other biological functions of RIG-I have emerged to extend the role of RIG-I as a PRR. Accumulating evidence has shown that RIG-I participates in cellular damage and the occurrence and development of many diseases, such as acute myeloid leukemia (AML), hepatocellular carcinoma, lupus nephritis, immunoglobulin A nephropathy, Crohn’s disease, rheumatoid arthritis, and cardiovascular diseases (CVD) ( 12 18 ).…”
Section: Introductionmentioning
confidence: 99%